Microstructure, mechanical properties and tribological behavior of a novel low-alloy high strength Mg–2Zn-0.5Zr-0.5Nd alloy. (September 2020) - Cai, Changhong; Song, Renbo; Peng, Shiguang; Wang, Yongjin; Li, Jingyuan
Abstract: A novel low-alloy high strength biodegradable Mg–2Zn-0.5Zr-0.5Nd alloy was fabricated through indirect extrusion under the extrusion ratio of 16:1, speed of 0.5 mm/s and temperature of 300 °C. The alloy exhibited good mechanical properties with tensile yield strength (TYS) of 353 MPa, ultimate tensile strength (UTS) of 362 MPa and elongation to failure (EL) of 15.3%. In addition, the coefficient of friction (COF) of 0.15 and wear rate of 3.9 × 10 −3 mm 3 N −1 m −1 in Hank's solution were obtained. Highlights: A novel low-alloy high strength Mg–2Zn-0.5Zr-0.5Nd alloy was fabricated through indirect extrusion. A good combination of TYS of 353 MPa, UTS of 362 MPa and EL of 15.3% was obtained. The COF of 0.15 and wear rate of 3.9 × 10 −3 mm 3 N −1 m −1 may have potential for artificial joint applications.